Differentiation in reproductive traits of geminate mangrove crabs of the genus Aratus (Decapoda: Brachyura) across the Central American Isthmus. (December 2016) - Rebolledo, Adriana P.; Wehrtmann, Ingo S.
Abstract: The mangrove crab Aratus pisonii was considered to have an amphi‐American distribution; however, a recent study revealed that the Eastern Tropical Pacific populations were genetically distinct, thus representing a new species: Aratus pacificus . These species separated by the Isthmus of Panama have diverged under different environmental conditions that may have influenced their reproductive biology. As the available information about this genus concerns almost exclusively the Caribbean species, the aim of the present study was to analyse and compare reproductive aspects of A . pacificus and A. pisonii obtained from both the Pacific and Caribbean coasts of Costa Rica. Females were collected from April 2011 to April 2012, and reproductive features such as breeding season, size distribution of ovigerous females, fecundity, reproductive output, embryo volume and embryo water content were assessed. Both species produced embryos during the entire sampled period. Most females of A. pacificus carrying embryos close to hatching were found during the rainy season. Ovigerous females of A. pisonii were substantially larger and reached sexual maturity at a larger size than females of A. pacificus . Embryo production started in A. pacificus at a smaller female size than in A. pisonii . As fecundity increased with female size, the average fecundity was lower in A. pacificus . Females of A. pisonii produced larger embryos, which might be related to lower food availability: higher energy content in the embryo enhances the chances of larval survival. These data regarding reproductive features of the Pacific and Caribbean species support the conclusion to separate A. pacificus from A. pisonii .